PENGARUH PROFESIONALISME, INDEPENDENSI, KOMITMEN ORGANISASI, DAN BUDAYA KERJA TERHADAP KINERJA INTERNAL AUDITOR DI BPKP PROVINSI - Muhammad Taufik Akbar; Hardi -; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This Research is aimed to know the effect of profesionalism , independence, organizational commitment and work culture to performance of internal auditors. This research is held at BPKP Riau province, The population of this study are internal auditors of BPKP. The data of this study are collected by using questionaires, and analyzed by using multiple regression. The result of this study shows that the professionalism, independence, organizational commitment and work culture have the possitive to the performent of internal auditors. The results also showed the contribution of independent variable influence on the dependent variable is equal to 82.1%. While the remaining 17.9% is influenced by other variables not included in this regression model.Keywords: Professionalism, independence, Organizational Commitment, Work Culture, and Performance of Internal Auditors.